2000
DOI: 10.1046/j.1365-2958.2000.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Formate protects stationary‐phase Escherichia coli and Salmonella cells from killing by a cationic antimicrobial peptide

Abstract: For a sustained infection, enteric bacterial pathogens must evade, resist or tolerate a variety of antimicrobial host defence peptides and proteins. We report here that specific organic acids protect stationary‐phase Escherichia coli and Salmonella cells from killing by a potent antimicrobial peptide derived from the human bactericidal/permeability‐increasing protein (BPI). BPI‐derived peptide P2 rapidly halted oxygen consumption by stationary‐phase cells preincubated with glucose, pyruvate or malate and cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 47 publications
3
67
0
Order By: Relevance
“…Expression effects mediated by formate could be involved in the phenomenon of formate protection from antimicrobial peptides (7). The absence of RpoS participation in formate protection is consistent with our finding of lowered steadystate activity of the RpoS regulon in cultures grown with formate.…”
Section: Discussionsupporting
confidence: 90%
“…Expression effects mediated by formate could be involved in the phenomenon of formate protection from antimicrobial peptides (7). The absence of RpoS participation in formate protection is consistent with our finding of lowered steadystate activity of the RpoS regulon in cultures grown with formate.…”
Section: Discussionsupporting
confidence: 90%
“…However, the fact that only adhC1 is iron regulated may suggest that the product of this gene plays a role additional to its well-established function in the detoxification of intracellular formaldehyde. It was recently reported that organic acids such as formate, which is produced by the successive enzymic action of GSH-FDH and S-formylglutathione hydrolase on formaldehyde, protect stationary-phase E. coli and Salmonella cells from killing by cationic peptides (Barker et al, 2000). Thus, a potential protective function of increased expression of GSH-FDH, which would result in higher intracellular levels of formate, is in agreement with the fact that pathogens such as A. baumannii encounter antimicrobial peptides produced by the host.…”
Section: Discussionmentioning
confidence: 99%
“…This region forms an amphipathic beta-turn and binds LPS (14,28). It has been proposed that BPI and P2, a peptide that contains BPI residues 86 to 104, may employ the same mechanism for killing Escherichia coli since both increase outer membrane (OM) permeability to hydrophobic compounds and inhibit O 2 consumption (2,21). The cytotoxic mechanism of BPI remains poorly understood.…”
mentioning
confidence: 99%
“…The released divalent ions are thought to activate bacterial phospholipases, leading to membrane rupture (26,29). It is also thought that BPI may damage the cytoplasmic membranes of the target cells (2,21,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation